Medication adherence in allergic diseases and asthma: a literature review - Malaya, Elizabeth; Piątkowska, Adrianna; Panek, Michał; Kuna, Piotr; Kupczyk, Maciej; Kardas, Grzegorz (Frontiers in Pharmacology, 2024)
Patients' collaboration with healthcare providers, along with their individual dedication to follow medical recommendations, is a crucial component of effective therapy in chronic diseases. Whether a patient fails to fill their prescription, administers the medication improperly in terms of method and/or dosage, misses follow-up visits or discontinues the treatment for any reason, these lapses can adversely affect the management of the disease, impairing the effectiveness of symptom relief and prevention of progression and complications. A comparable situation pertains to allergic diseases, which require long-term and consistent treatment to achieve symptom alleviation and control. Research has shown that adherence rates for long-term therapy in chronic diseases had improved marginally over the years and continue to hover around the figure published in a World Health Organization (WHO) report “Adherence to long-term therapies: evidence for action.” from 2003, which had stated that only 50% of patients in developed countries follow medical recommendations and that this rate would be even lower in developing countries. Over 20 years later literature indicated that there has been only a slight improvement on the matter, leaving room for developing and implementing effective solutions to improve medication compliance. Further investigation on this matter is required. Causes for non-adherence classified by Global Initiative for Asthma in their main report seem to correspond to those of WHO’s report. Similar dependency might be determined by other allergic diseases as they fit chronic diseases criteria, and the issue of non-adherence affects them too. This literature review seeks to compile and synthesize current insights on factors that influence adherence, as well as explore potential methods for monitoring, evaluating and improving its outcomes in chronic diseases related to the medical field of allergology, such as: asthma, allergic rhinitis, allergic conjunctivitis, rhinoconjunctivitis, atopic dermatitis and urticaria.